Words and Collocations Containing roots -gr(i)eg- (-gring-, -grec-, etc.), -helen-, -bizant- in Modern Spanish - Stefanchikov, Igor Vyacheslavovich (Litera, 2022)
The article addresses the subject of the semantics of Spanish words and collocations containing the roots -gr(i)eg- (-grec-, -gring-, etc.), -helen-, -bizant-, associated with Greece and with the Greek culture. The author analyzes the semantics and etymology of the words and expressions the way they are represented in the two most reputable explanatory dictionaries, Diccionario de la lengua española (DLE) and Diccionario de americanismos. In some cases, the usage of the selected units is described with reference to corpus data (Modern Spanish corpora — CREA and CORPES XXI). The study has revealed the presence of a significant proportion of “learned borrowings” (“cultismos”), which is explained by the importance of Ancient Greek and Byzantine culture for European civilization in general and for Spain in particular. It is stated that the semantic evolution of some vocabulary units was influenced by stereotypical ideas about Greece and the Greeks. In addition, the analysis of Diccionario de americanismos has shown some peculiarities of the usage of the words and expressions under analysis in Latin American Spanish (e. g. the more frequent use of “gringo” and its derivatives).